Management of Patient with Neuroleptic Malignant Syndrome - Ginarsyah, Riando; Anggraeni, Novita (CV. Publikasi Indonesia, 2025)
Neuroleptic Malignant Syndrome (NMS) is a rare, life-threatening condition often induced by the use of antipsychotic drugs, characterized by hyperthermia, muscle rigidity, altered mental status, and autonomic dysfunction. This syndrome can be precipitated by antipsychotic medications, including haloperidol and fluphenazine, or by abrupt withdrawal of dopaminergic medications. This case report presents the management of a 56-year-old male patient admitted with decreased consciousness, muscle rigidity, and high fever, diagnosed with NMS. The patient was treated with supportive care, electrolyte correction, and medications including ceftriaxone, resfar, omeprazole, and others. The patient’s condition gradually improved with proper monitoring, and after intensive care, the patient was transferred to the ward. This report highlights the importance of early detection, discontinuation of causative drugs, and appropriate therapeutic interventions to reduce the mortality rate, which remains high at 20-30% if untreated. The treatment approach emphasizes symptom management, including fluid resuscitation and the use of medications like bromocriptine or dantrolene for severe cases.